2020
DOI: 10.1002/ppul.24772
|View full text |Cite
|
Sign up to set email alerts
|

Changes in respiratory mechanics at birth in preterm infants: A pilot study

Abstract: Objective We aimed to measure lung mechanics at birth by the forced oscillation technique (FOT) for assessment of the initial degree of lung aeration and the short‐term aeration changes after applying different respiratory support strategies. Methods Eighteen preterm infants (gestational age = 29‐36 week) were randomized to receive either continuous positive airway pressure (CPAP) at 5 cmH2O only or combined with a sustained inflation (SI; 15 seconds at 25 cmH2O after 5 seconds of CPAP) at birth. We assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…The technique does not involve estimating the pleural pressure by positioning an oesophagal balloon or evoking the Hering–Breuer inflation reflex for respiratory muscle relaxation. Previous studies demonstrated FOT feasibility in the delivery room [ 31 ] and the NICU, both in intubated patients [ 27 29 ] and infants receiving NCPAP [ 30 ]. Moreover, thanks to recent technological advancements, oscillometry can be now integrated into modern mechanical ventilators.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The technique does not involve estimating the pleural pressure by positioning an oesophagal balloon or evoking the Hering–Breuer inflation reflex for respiratory muscle relaxation. Previous studies demonstrated FOT feasibility in the delivery room [ 31 ] and the NICU, both in intubated patients [ 27 29 ] and infants receiving NCPAP [ 30 ]. Moreover, thanks to recent technological advancements, oscillometry can be now integrated into modern mechanical ventilators.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, studies demonstrated that the total respiratory system reactance (Xrs) measured at frequencies lower than 10 Hz at a given distending pressure is a sensitive and specific indicator of lung volume recruitment [ 19 , 24 ]. FOT measurements are suitable at the bedside in preterm infants during invasive [ 25 29 ] and non-invasive respiratory support [ 30 ], and even during respiratory stabilization in the delivery room [ 31 ]. Moreover, oscillometry assessments in the first few days of life can predict respiratory support duration [ 27 , 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…Their observation that male infants had increased elastance (reduced compliance) may reflect delayed alveolar development, but the variability of the measurements was quite high, and the study sample was quite modest. 1 Veneroni et al 2 tested whether or not sustained inflation at birth (vs. nCPAP) in prematures in mild respiratory distress would durably alter mechanics measured by forced oscillation, finding, as in the study by Kim et al, 1 that the variability of measurements is quite high, with no discernible difference between the two strategies. Given the large changes in lung alveolar fluid that take place at the time of birth, this is to be expected.…”
Section: Neonatal Lung Mechanics/ Physiologymentioning
confidence: 99%
“…Veneroni, et al used FO to compare respiratory mechanics in preterm infants treated with continuous positive airway pressure (CPAP) versus CPAP with sustained inflations of 25 cmH2O for 15 seconds [5]. Infants presented with highly heterogeneous degrees of lung aeration at birth, limiting their ability to use FO to assess ventilation strategies.…”
Section: Forced Oscillometrymentioning
confidence: 99%